2018
DOI: 10.1021/acs.jmedchem.8b00797
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomerism by Design: Discovery of a Selective and Stable Phosphoinositide 3-Kinase (PI3K) β Inhibitor

Abstract: Atropisomerism is a type of axial chirality in which enantiomers or diastereoisomers arise due to hindered rotation around a bond axis. In this manuscript, we report a case in which torsional scan studies guided the thoughtful creation of a restricted axis of rotation between two heteroaromatic systems of a phosphoinositide 3-kinase (PI3K) β inhibitor, generating a pair of atropisomeric compounds with significantly different pharmacological and pharmacokinetic profiles. Emblematic of these differences, the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 36 publications
(19 reference statements)
0
49
0
Order By: Relevance
“…[15,54] Calculationso n1 using the MMFF force field and at the B3LYP/6-31G** level complemented variabletemperature NMR measurements that suggestabarrier to rotation of 35 kcal mol À1 . [22] Removal of the methyl on the imidazole ring was computed to lower the barrier to about 17 kcal mol À1 consistentw ith the observation of free rotation. Another combined experimental and computational study of 21 and 22 revealed the significant effect of ring expansion on racemisation rate (Table 3).…”
Section: Rotationa Bout Single Bondsmentioning
confidence: 59%
See 4 more Smart Citations
“…[15,54] Calculationso n1 using the MMFF force field and at the B3LYP/6-31G** level complemented variabletemperature NMR measurements that suggestabarrier to rotation of 35 kcal mol À1 . [22] Removal of the methyl on the imidazole ring was computed to lower the barrier to about 17 kcal mol À1 consistentw ith the observation of free rotation. Another combined experimental and computational study of 21 and 22 revealed the significant effect of ring expansion on racemisation rate (Table 3).…”
Section: Rotationa Bout Single Bondsmentioning
confidence: 59%
“…Compounds with barriers at the HF/6‐31G** level below about 20 kcal mol −1 or above approximately 30 kcal mol −1 can be developed as single compounds, whereas those in between these two extremes are likely to form mixtures with a time dependence that is comparable to storage and dosing of drugs . Variations on this approach have been described subsequently …”
Section: Tools To Understand and Predict Racemisation Ratesmentioning
confidence: 94%
See 3 more Smart Citations